Selection of Bali cattle based on birth weight and calving interval records at West Nusa Tenggara Province of Indonesia - Said, S.; Putra, W. P. B.; Muzawar, M.; Kantong, S. A. (Diponegoro University, 2020)
Birth weight and calving interval are included of productivity traits that can be increased by selection program. However, the standard of desirable birth weight in cattle during the selection program is important to prevent dystocia incident risk. This study was aimed to select Bali cattle (Bos javanicus) based on Estimated Breeding Value of birth weight (EBVBW) and Most Probable Producing Ability of birth weight (MPPABW) and calving interval (MPPACI). Total of 758 records data of BW were collected from Lombok and Sumbawa islands, West Nusa Tenggara Province. Research showed the average of BW in Bali calves were 15.69±1.70 kg (Lombok) and 13.49±1.89 (Sumbawa). The average of CI in Bali cows at both islands were about 385 days. In addition, the heritability (h2) values of BW in both islands was about 0.90. The repeatability (r) values of BW in both islands were about 0.30. Meanwhile, the r value of CI in Sumbawa island was 0.39. The highest of EBVBW for sire was +4.25 kg by bull’s ID: 0838 (Sumbawa). Meanwhile, the highest of EBVBW for calves was +6.07 kg by calf’s ID: 0917 (Sumbawa). The highest of MPPABW was +2.67 kg by cow’s ID: 0872 (Sumbawa). The lowest of MPPACI was -25.70 days by cow’s ID: 02076 (Lombok).